A method for producing an iron-based amorphous alloy strip
Patent Information
- Application Number
- CN202611274825.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-16
AI Technical Summary
[0009]为了解决现有技术的不足,本发明提出了一种铁基非晶合金带材的制备方法,有效解决了传统工艺中熔体纯净度不够、带宽厚度偏差大、收卷不稳定、成材率低的问题
(1)本申请在熔炼和快淬之间加入了一个中间包二次精炼环节,形成了初炼、精炼、保温三级钢液处理体系,每级都独立控温和氩气保护,中间包这一步给了夹杂物充分上浮的时间,成分和温度也更加均匀,钢液进喷包之前的纯净度和稳定性明显提升;
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure REF-OBJ-1787280495204-000003
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials preparation technology, and more particularly to amorphous alloys, specifically a method for preparing high-performance iron-based amorphous alloy strips. Background Technology
[0002] Iron-based amorphous alloy strips are widely used in power distribution transformers, motor cores, and other fields due to their excellent soft magnetic properties (low coercivity, high permeability, and low iron loss). Currently, the main industrial production method for iron-based amorphous strips is the single-roll rapid quenching method, which involves: raw material melting, heat preservation, direct strip spraying, and winding. Taking a typical traditional process as an example: after the raw material is melted in a melting furnace, the molten steel is held at a constant temperature in the furnace for a period of time, and then directly poured into a nozzle, sprayed onto the surface of a rotating copper roller for rapid cooling and forming. The strip is then wound up by mechanical gripping or simple negative pressure adsorption.
[0003] This process is mature and the equipment structure is simple. Its advantages include low investment cost and low operating threshold, making it suitable for small-batch trial production and applications where the requirements for strip quality are not high. However, the problems with this process become very obvious in large-scale continuous production.
[0004] Firstly, the molten steel only undergoes a single static settling process from smelting to strip spraying, resulting in insufficient inclusion flotation and composition homogenization. During the transfer process, the molten steel comes into contact with air, making secondary oxidation difficult to avoid. Once oxidized inclusions enter the nozzle, they can affect the stability of the spray flow, or even clog the nozzle and cause strip breakage. The inclusions themselves can also become heterogeneous nucleation sites, reducing the amorphous forming ability of the molten steel, leading to localized crystallization of the strip and a decrease in toughness.
[0005] Secondly, the temperature field and composition field of the molten steel after single-stage heat preservation are not actually uniform. The viscosity of the melt fluctuates greatly when spraying the strip, and the thickness deviation of the strip can usually only be ±5μm. When making wide strips, it is common for the thickness difference between the edge and the middle to be 10%, which affects the subsequent lamination and magnetic properties.
[0006] Thirdly, winding is a major problem. Amorphous ribbon is inherently brittle, with a thickness of only 20 to 30 micrometers. When it is lifted off the copper roller at a linear speed of 20 to 30 meters per second, the ribbon vibrates severely. Conventional mechanical clamping or simple suction negative pressure methods have low success rates in gripping, and the tension is unstable. Rib breakage, deviation, and scratches frequently occur, and the yield rate can often only be maintained at around 85%.
[0007] Fourth, at the nozzle exit section, the molten steel comes into contact with air as soon as it is sprayed out, and the surface oxidizes rapidly. The surface quality of the strip is poor, and the oxide scale accumulated on the copper roller will worsen the heat transfer, which in turn affects the control of amorphousness and thickness.
[0008] The combination of these problems means that the consistency of strip material and the yield rate remain a bottleneck in continuous and large-scale production using traditional processes. Summary of the Invention
[0009] To address the shortcomings of existing technologies, this invention proposes a method for preparing iron-based amorphous alloy strips, which effectively solves the problems of insufficient melt purity, large deviation in strip width and thickness, unstable winding, and low yield in traditional processes.
[0010] The technical problem to be solved by the present invention is achieved through the following technical solution: A method for preparing an iron-based amorphous alloy strip includes the following steps: S1 Batching and Primary Refining: After weighing industrial pure iron, silicon, and ferroboron according to the target composition, add them sequentially to the medium-frequency induction melting furnace, melt and remove slag under argon protection, refine at 1300-1380℃ and hold for 10-15 min, take samples to test the composition and obtain primary refined molten steel. S2 Tundish Refining and Temperature Control: The primary molten steel is transferred to the tundish under argon protection throughout the process, and then subjected to secondary refining and temperature control at 1350-1480℃ under argon protection. S3 Spraying and Rapid Quenching: Molten steel is injected into a preheated spraying ladle at 1350℃ under controlled flow. It is continuously sprayed from the spraying ladle nozzle onto the surface of a rotating copper roller with a linear velocity of 20-25 m / s. The gap between the nozzle and the copper roller is controlled at 0.3-0.9 mm. The molten steel flows at a rate ≥10... 6 The amorphous ribbon is rapidly solidified at a cooling rate of ℃ / s; during the spraying process, a protective gas of 0.10-0.50MPa is applied behind the nozzle. S4 strip online winding: The amorphous strip stripped from the copper roller is gripped onto the winding sleeve by negative pressure adsorption, and wound up with constant tension synchronized with the linear speed of the copper roller. In the early stage of winding, pressure rollers are used to help increase the contact area between the strip and the copper roller.
[0011] In this invention, the mass percentage of the target components in step S1 is: Fe 92.65%-93.70%, Si 3.7%-4.3%, B 2.4%-2.8%, C 0.20%-0.30%, and S≤0.005% and P≤0.01%; preferably, Fe: 92.95%, Si: 4.1%, B: 2.7%, C: 0.25%, wherein the silicon source is selected from elemental silicon and ferrosilicon.
[0012] In step S1, the raw materials are added in the following order: silicon, ferroborone, carbon powder, and industrial pure iron, with a melting temperature of 1450-1480℃. The micro-alloying effect of carbon powder can reduce the viscosity of the molten iron, promote the rapid dissolution and uniform diffusion of silicon and ferroborone, and reduce component segregation. At the same time, adding alloying elements and carbon powder first, followed by pure iron, can further improve the alloying efficiency by utilizing the latent heat of pure iron melting, and reduce the burn-off of easily oxidized elements.
[0013] In steps S1 and S2, argon gas is used to maintain a weak positive pressure of 0.02-0.05 MPa. This weak positive pressure blocks external air without forcing gas into the molten steel and creating pores.
[0014] In step S3, the copper roller is a beryllium copper alloy roller with internal water forced cooling. Beryllium copper has good thermal conductivity and resistance to thermal fatigue, making it suitable for long-term continuous operation.
[0015] In step S3, the adjustment accuracy of the gap between the nozzle and the copper roller is controlled within ±0.05 mm.
[0016] In step S3, carbon monoxide is used as the protective gas. Carbon monoxide is reducing at high temperatures, creating a localized protective atmosphere at the nozzle outlet, which reduces oxidation on the cylinder surface and facilitates the strip stripping from the copper roller. The carbon monoxide-containing exhaust gas generated during the injection process is uniformly treated by a gas collection hood located in the contact area between the nozzle and the copper roller. After being led out through the exhaust pipe, it is sent to the exhaust gas treatment device, where the carbon monoxide is rendered harmless through ignition, catalytic oxidation, or a combination of both.
[0017] In step S4, negative pressure adsorption is initiated 10 mm from the copper roller. After successful gripping, constant tension winding begins, and the water-cooled roller simultaneously provides contact-type auxiliary cooling to the strip and monitors the thickness online.
[0018] In step S4, when a single roll reaches 750 kg, the tape breaks and the roll is unloaded. Then, the next roll is grabbed, and production continues.
[0019] The present invention also provides an iron-based amorphous alloy strip prepared by the above method. The iron-based amorphous alloy strip prepared has an average thickness of 23-27 μm, a thickness deviation of ≤±4 μm, and preferably a thickness deviation of ≤2 μm under the working conditions. After annealing, the saturation magnetic induction intensity Bs is 1.45-1.55 T, the coercivity Hc does not exceed 2.5 A / m, and the iron loss P at 1.35T / 50Hz does not exceed 0.15 W / kg.
[0020] Compared with the prior art, the present invention has the following advantages: (1) This application adds a secondary refining step in an intermediate ladle between smelting and rapid quenching, forming a three-stage steel liquid treatment system of primary refining, refining and heat preservation. Each stage is independently temperature controlled and protected by argon. The intermediate ladle step gives the inclusions sufficient time to float, and the composition and temperature are more uniform. The purity and stability of the steel liquid before entering the ladle are significantly improved. (2) From the feeding and melting to the tundish tapping and then to the spraying and stripping, the entire line of this application maintains a weak positive pressure of argon gas, and the molten steel does not come into contact with air throughout the process, which solves the problem of secondary oxidation from the root. A carbon monoxide protection is added after the nozzle to form a local reducing atmosphere at the point when the molten steel is just sprayed out and the cooling is fastest. (3) This application has determined the working range and matching relationship of three key parameters, namely, the linear speed of the copper roller, the nozzle gap and the CO protective gas pressure, through experiments. Under the preferred parameter combination, the spreading and cooling of the molten steel are well matched, the thickness deviation of the strip can be controlled within ±2 μm, and the surface roughness Ra does not exceed 0.5 μm. (4) In this application, a combination of negative pressure adsorption gripping, constant tension synchronous winding, and pressure roller assistance is used in the winding process. The negative pressure ensures that the material can be gripped at the beginning, and the pressure roller increases the adhesion between the strip and the copper roller in the initial stage to reduce swaying and shaking. The constant tension control makes the whole roll tight and loose. According to actual production statistics, the yield of continuous production can reach more than 95%. (5) This application improves the dissolution effect of silicon and boron elements in iron melt by introducing 0.20%-0.30% carbon element into the formula for microalloying control, further enhances the uniformity of melt composition, strengthens the amorphous formation ability, and significantly optimizes the magnetic properties and toughness of the strip.
[0021] (6) The strip prepared by the scheme of this application has a saturation magnetic induction intensity Bs of 1.45-1.55 T after annealing, a coercivity Hc of no more than 2.5 A / m, and an iron loss P of no more than 0.15 W / kg at 1.35T / 50Hz. Attached Figure Description
[0022] Figure 1 This is a process flow diagram of the present invention; Figure 2 This is a graph showing the relationship between the linear speed of the copper roller and the strip thickness / thickness deviation in this invention; Figure 3 This is a diagram showing the relationship between nozzle gap and strip thickness / surface roughness in this invention; Figure 4 This is a graph showing the relationship between CO protective gas pressure and surface oxygen content / yield in this invention; Figure 5 This is a comparison of XRD patterns between the present invention and existing technologies; Figure 6 This is a performance comparison chart between the present invention and existing technologies. Detailed Implementation
[0023] The present invention will be further described below with reference to the accompanying drawings and specific preferred embodiments, but this does not limit the scope of protection of the present invention.
[0024] Unless otherwise specified, the raw materials, equipment, and testing standards used in the embodiments of this invention are all commercially available products, conventional industrial equipment, and national / industry general standards in the field.
[0025] Example 1
[0026] This embodiment provides a preferred method for preparing iron-based amorphous alloy strip, specifically as follows: Figure 1 As shown.
[0027] S1 Batching and Primary Refining: Target composition: Fe 92.95%, Si 4.1%, B 2.7%, C 0.25%. Weigh out 6600 kg of industrial pure iron, 329 kg of elemental silicon, 1085 kg of ferroborone (containing 20% B), and 20 kg of high-purity carbon powder. First, add elemental silicon, ferroborone, pure iron, and carbon powder sequentially to the crucible of a medium-frequency induction melting furnace. Melt by powering up the furnace, gradually increasing the power until the temperature reaches 1300℃. Maintain a weak positive pressure of 0.03 MPa with argon gas inside the furnace. After complete melting, remove the slag, raise the temperature to 1480℃ and hold for 12 min for refining. Take a sample for spectral analysis; the composition is qualified.
[0028] S2 Tundish Refining and Temperature Control: The primary molten steel is transferred to the tundish under argon protection. The tundish temperature is controlled to 1480℃, and argon is used to maintain a positive pressure of 0.03 MPa for secondary refining and heat preservation. Then, the tundish outlet is connected to the ladle inlet, which has been preheated to 1350℃.
[0029] S3 Spraying and Controlled Flow Forming: The beryllium copper alloy roller is pre-raised to a linear velocity of 22 m / s and internally cooled by water. The gap between the nozzle and the roller is adjusted to 0.5 mm. Molten steel from the tundish is injected into the spraying ladle under controlled flow, continuously sprayed onto the surface of the roller from the nozzle. Simultaneously, carbon monoxide protective gas is sprayed at a pressure of 0.25 MPa in the area behind the gap between the nozzle and the roller. The carbon monoxide gas flow is close to the surface of the roller, working in conjunction with the global inert atmosphere formed by argon protection to form a localized reducing protective thin layer at the interface of rapid solidification of the molten steel. The resulting mixed exhaust gas containing carbon monoxide and carbon dioxide is collected and treated by a gas collection hood located in the nozzle area. The molten steel on the surface of the roller reaches a pressure of ≥10... 6 Cooling and forming at a rate of ℃ / s.
[0030] S4 strip online winding: Negative pressure adsorption is initiated 10 mm from the copper roller to grip the strip onto the winding sleeve. After successful gripping, winding begins with constant tension synchronized with the linear speed of the copper roller. Pressure rollers assist in increasing the contact area between the strip and the copper roller, while water-cooled rollers provide contact-assisted cooling of the strip deep within the roll and monitor the thickness online. The strip is broken and unwound when it reaches 750 kg, and then sent to a rewinding process.
[0031] S5 test results: The XRD pattern shows broad, diffuse peaks without sharp crystallization peaks. It is completely amorphous. The average thickness of the strip is 25 μm, with a thickness deviation ≤ ±2 μm, and a surface roughness Ra of 0.42 μm. After annealing at 380℃ under nitrogen protection for 120 min, the strip sample exhibits a saturation magnetic induction intensity Bs of 1.48 T, a coercivity Hc of 2.2 A / m, and an iron loss P of 0.13 W / kg at 1.35 T / 50 Hz; it does not crack when folded at 180°; the yield rate in continuous production is 96.5%.
[0032] Example 2
[0033] This embodiment is based on Embodiment 1, and a new implementation case is formed by making appropriate adjustments to the target components.
[0034] The difference from Example 1 is that in step S1, the target composition is adjusted to Fe 93.55%, Si 3.7%, B 2.5%, and C 0.25%, with the balance and impurity control remaining the same as in Example 1. The resulting strip has an average thickness of 24.7 μm, a thickness deviation of ≤±3 μm, and after annealing, Bs 1.52 T, Hc 2.3 A / m, and iron loss P 0.14 W / kg; the continuous production yield is 95.8%.
[0035] Example 3
[0036] This embodiment is based on Embodiment 1, and a new implementation case is formed by making appropriate adjustments to the target components.
[0037] The difference from Example 1 is that in step S1, the target composition is adjusted to Fe 92.75%, Si 4.2%, B 2.8%, and C 0.25%, with the balance and impurity control remaining the same as in Example 1. The resulting strip has an average thickness of 25.3 μm, a thickness deviation of ≤±2 μm, and after annealing, Bs 1.46 T, Hc 2.4 A / m, and iron loss P 0.14 W / kg; the yield rate in continuous production is 95.9%.
[0038] Example 4
[0039] This embodiment sets up a comparative experiment to verify the rationality of the parameter working range by adjusting key parameters such as copper roller linear speed, nozzle gap, and CO protective gas pressure.
[0040] 1. Scale settings Comparative Example 1-1: The linear speed of the copper roller is lower than that of the present invention. The difference from Example 1 is that in step S3, the linear speed of the copper roller is adjusted to 18 m / s, while the other parameters remain unchanged. The resulting strip has an average thickness of 32.6 μm and a thickness deviation of ±5 μm; after annealing, Bs is 1.41 T, Hc is 3.6 A / m, and iron loss P is 0.20 W / kg; the yield is 87%.
[0041] When the linear velocity is too low, the cooling rate is insufficient, the strip thickness increases and becomes uneven, the degree of amorphous formation decreases, and the magnetic properties deteriorate.
[0042] Comparative Examples 1-2: The linear speed of the copper roller is higher than that of this invention. The difference from Example 1 is that in step S3, the linear speed of the copper roller is adjusted to 30 m / s, while the other parameters remain unchanged. The resulting strip has an average thickness of 21.8 μm and a thickness deviation of ±4 μm; after annealing, Bs is 1.43 T, Hc is 3.1 A / m, and iron loss P is 0.18 W / kg; the yield is 89%.
[0043] If the linear speed is too high, the molten steel will spread excessively, the strip will be too thin and prone to micropores, making thickness control difficult and reducing the yield.
[0044] Comparative Examples 1-3: Nozzle gaps are smaller than those of the present invention. The difference from Example 1 is that in step S3, the gap between the nozzle and the copper roller is adjusted to 0.1 mm, while the other parameters remain unchanged. The resulting strip has an average thickness of 24.1 μm, obvious longitudinal scratches on the surface, and a thickness deviation of ±5 μm; after annealing, Bs is 1.43 T, Hc is 3.2 A / m, and iron loss P is 0.19 W / kg; the yield is 87%.
[0045] If the gap is too small, the nozzle is prone to interference with the copper roller, which restricts the flow of molten steel, results in poor strip surface quality, and reduces process stability.
[0046] Comparative Examples 1-4: Nozzle gaps are larger than the scope of this invention. The difference from Example 1 is that in step S3, the gap between the nozzle and the copper roller is adjusted to 1.2 mm, while the other parameters remain unchanged. The resulting strip has an average thickness of 33.5 μm and a thickness deviation of ±6 μm; after annealing, Bs is 1.41 T, Hc is 3.8 A / m, and iron loss P is 0.21 W / kg; the yield is 85%.
[0047] Excessive gaps lead to uneven spreading of molten steel, reduced cooling rate, large fluctuations in strip thickness, and decreased amorphous formation.
[0048] Comparative Examples 1-5: CO protective gas pressure is lower than the range of this invention. The difference from Example 1 is that in step S3, the carbon monoxide pressure was adjusted to 0.02 MPa, while the other parameters remained unchanged. The resulting strip had intermittent oxide spots on its surface, with a surface roughness Ra of 0.85 μm; after return, Bs was 1.44 T, Hc was 2.8 A / m, and iron loss P was 0.17 W / kg; the yield was 92%.
[0049] Insufficient protective air pressure, inadequate reducing atmosphere at the nozzle outlet, obvious oxidation on the strip surface, and substandard appearance quality.
[0050] Comparative Examples 1-6: CO protective gas pressure is higher than the range of this invention. The difference from Example 1 is that in step S3, the carbon monoxide pressure was adjusted to 0.80 MPa, while the other parameters remained unchanged. The resulting strip surface showed traces of carbon deposits, and black deposits appeared on the copper roller surface; after annealing, Bs was 1.44 T, Hc was 2.7 A / m, and iron loss P was 0.16 W / kg; the yield was 91%.
[0051] Excessive gas pressure leads to excessive CO supply, causing carbon produced by decomposition to accumulate on the surface of the copper roller, affecting heat transfer and increasing the load on exhaust gas treatment, thus reducing economic efficiency.
[0052] 2. Performance Comparison (Table 1) Table 1 shows the performance comparison of the invention across a single parameter range.
[0053] 3. Results Analysis (1) Copper roller linear speed: When it is below 20 m / s (Comparative Example 1-1) or above 25 m / s (Comparative Example 1-2), the strip thickness deviation increases significantly, the magnetic properties decrease, and the yield decreases. 20-25 m / s is a reasonable range to ensure strip quality and production stability. Figure 2 ).
[0054] (2) Nozzle gap: When it is less than 0.3 mm (Comparative Examples 1-3), scratches appear on the strip surface and the thickness fluctuates greatly; when it is greater than 0.9 mm (Comparative Examples 1-4), the strip is too thick and the deviation is large. 0.3-0.9 mm is a reasonable range that balances thickness accuracy and surface quality. Figure 3 ).
[0055] (3) CO protective gas pressure: When it is below 0.10 MPa (Comparative Examples 1-5), the protection is insufficient and the surface is oxidized; when it is above 0.50 MPa (Comparative Examples 1-6), carbon buildup occurs on the copper roller, affecting heat transfer. 0.10-0.50 MPa is a reasonable range for balancing the protective effect and process stability. Figure 4 ).
[0056] Example 5
[0057] This embodiment includes a control experiment to compare the technical solution of the present invention with the prior art and verify the technical effect of the present invention.
[0058] 1. Comparison Case Setup Comparative Example 2-1: Traditional Process Using existing traditional processes, there is no intermediate ladle for secondary refining. Only the melting furnace is filled with argon for protection. There is no argon gas coverage throughout the transfer and spraying process. No carbon monoxide is passed behind the nozzle. The copper roller linear speed is 30 m / s, the nozzle gap is 0.5 mm, no carbon element is actively added, the carbon content is ≤0.08%, silicon and ferroborone are not fully dissolved, and the melt composition is highly segregated, which further aggravates the strip thickness fluctuation and magnetic property deterioration. The winding adopts a conventional mechanical gripping method.
[0059] This process involves simple equipment and low investment, making it suitable for small-batch trial production. However, due to the lack of tundish refining and full-process protection, the purity and temperature uniformity of the molten steel are insufficient, resulting in large fluctuations in strip quality. The average thickness of the obtained strip is 30.2 μm, but the deviation reaches ±6 μm, and the surface roughness Ra is 1.5 μm; after annealing, Hc is 4.5 A / m, iron loss P is 0.22 W / kg, and fracture occurs when folded at 180°. The yield rate for continuous production is only 82%.
[0060] 2. Performance Comparison (Table 2) Table 2 shows a performance comparison between Examples 1, 2, and 3 of the present invention and Comparative Example 2-1.
[0061] 3. Results Analysis The various indicators of the embodiments of the present invention are significantly better than those of the traditional process of the prior art (Comparative Example 2-1), indicating that the present invention achieves a comprehensive improvement in strip thickness accuracy, surface quality, magnetic properties and yield through the combined effects of a three-stage melting system, full-process argon protection, CO local reduction protection, synergistic control of key parameters and composite coiling method.
[0062] Figure 5 The XRD patterns of Example 1 and Comparative Example 2-1 are shown. Example 1 shows broad diffuse peaks, while Comparative Example 2-1 shows weak and sharp peaks superimposed on the diffuse peaks, indicating the presence of local crystallization. Figure 6 The graph shows a performance comparison between Example 1 and Comparative Example 2-1. It can be clearly seen that, compared with Comparative Example 2-1, Example 1 has a thickness deviation that has decreased from ±6 μm to ≤±2 μm, Hc that has decreased from 4.5 A / m to 2.2 A / m, iron loss that has decreased from 0.22 W / kg to 0.13 W / kg, and yield that has increased from 82% to 96.5%.
Claims
1. A method for preparing an iron-based amorphous alloy strip, characterized in that, Includes the following steps: S1 Batching and Primary Refining: After weighing industrial pure iron, silicon, and ferroboron according to the target composition, add them sequentially to the medium-frequency induction melting furnace, melt and remove slag under argon protection, refine at 1450-1480℃ and hold for 10-15 min, take samples to test the composition and obtain primary refined molten steel. S2 Tundish Refining and Temperature Control: The primary molten steel is transferred to the tundish under argon protection throughout the process, and then subjected to secondary refining and temperature control at 1350-1480℃ under argon protection. S3 Spraying and Rapid Quenching: Molten steel is injected into a preheated spraying ladle at 1350℃ under controlled flow. It is continuously sprayed from the spraying ladle nozzle onto the surface of a rotating copper roller with a linear velocity of 20-25 m / s. The gap between the nozzle and the copper roller is controlled at 0.3-0.9 mm. The molten steel flows at a rate ≥10... 6 The amorphous ribbon is rapidly solidified at a cooling rate of ℃ / s; during the spraying process, a protective gas of 0.10-0.50 MPa is applied behind the nozzle. S4 strip online winding: The amorphous strip stripped from the copper roller is gripped onto the winding sleeve by negative pressure adsorption, and wound up with constant tension synchronized with the linear speed of the copper roller. In the early stage of winding, pressure rollers are used to help increase the contact area between the strip and the copper roller.
2. The preparation method according to claim 1, characterized in that, The target components described in S1 have the following mass percentages: Fe 92.65%-93.70%, Si 3.7%-4.3%, B 2.4%-2.8%, C 0.20%-0.30%, and S≤0.005% and P≤0.01%.
3. The preparation method according to claim 2, characterized in that, The target components are expressed in the following mass percentages: Fe: 92.95%, Si: 4.1%, B: 2.7%, C: 0.25%.
4. The preparation method according to claim 1, characterized in that, The order of adding raw materials in S1 is silicon, ferroboron, carbon powder, and industrial pure iron, with a melting temperature of 1450-1480℃.
5. The preparation method according to claim 1, characterized in that: In S1 and S2, argon gas protection maintains a weak positive pressure of 0.02-0.05 MPa.
6. The preparation method according to claim 1, characterized in that, In S3, the adjustment accuracy of the gap between the nozzle and the copper roller is controlled within ±0.05 mm.
7. The preparation method according to claim 1, characterized in that, In S3, carbon monoxide is used as the protective gas.
8. The preparation method according to claim 1, characterized in that, In S4, negative pressure adsorption is initiated 10 mm from the copper roller. After successful gripping, constant tension winding begins, and the water-cooled roller simultaneously provides contact-type auxiliary cooling to the strip and monitors the thickness online.
9. A type of iron-based amorphous alloy strip prepared by the preparation method according to any one of claims 1-8, characterized in that, The average thickness of the strip is 23-27 μm, the thickness deviation is ≤±4 μm, and the coercivity Hc≤4 A / m.